2019
DOI: 10.7150/ijms.35267
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ahmed Glaucoma Valve Implantation on Neovascular Glaucoma

Abstract: To evaluate the efficacy of Ahmed glaucoma valve (AGV) implantation in treating neovascular glaucoma (NVG) and analyze the factors influencing the surgical success rate, a retrospective investigation of 59 NVG patients (66 eyes) who underwent AGV implantation was conducted at Jiangsu Province Hospital, China, from January 2014 to June 2018. Intraocular pressure (IOP), visual acuity, surgical success rates, medications, and complications were monitored at post-operative 1 day, 1 week, 1, 3, 6 and 12 months. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 28 publications
4
22
3
1
Order By: Relevance
“…One study reported a 73% success rate in 38 eyes that received a glaucoma drainage device and had relatively few postoperative complications 51 . However, this report is the exception as others have found 24,[48][49][50] . Our integrative surgical approach avoided tube-specific complications (e.g., tube exposure, retraction, corneal touch, obstruction), ranging from 13% to 26% in NVG over five years 24,[48][49][50][51] .…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…One study reported a 73% success rate in 38 eyes that received a glaucoma drainage device and had relatively few postoperative complications 51 . However, this report is the exception as others have found 24,[48][49][50] . Our integrative surgical approach avoided tube-specific complications (e.g., tube exposure, retraction, corneal touch, obstruction), ranging from 13% to 26% in NVG over five years 24,[48][49][50][51] .…”
Section: Discussioncontrasting
confidence: 84%
“…However, this report is the exception as others have found 24,[48][49][50] . Our integrative surgical approach avoided tube-specific complications (e.g., tube exposure, retraction, corneal touch, obstruction), ranging from 13% to 26% in NVG over five years 24,[48][49][50][51] . It delivers both retina and glaucoma treatment in a single surgical session and reduces the patient and health care system burden by simplifying postoperative care and follow-up.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Our success rate of 65%, defined as an IOP <22 mmHg, with or without glaucoma medication and without vision loss after a one-year follow-up, is similar to success rates reported for glaucoma drainage devices, which range from 62% to 66.7% 24 , 48 50 . One study reported a 73% success rate in 38 eyes that received a glaucoma drainage device and had relatively few postoperative complications 51 .…”
Section: Discussionsupporting
confidence: 83%
“…Many studies had been done to compare the efficacy of Ahmed glaucoma valve surgery and Trabeculectomy with Mitomycin-C and the success rate for glaucoma drainage devices which are reported in different studies vary from 31% to 97%. [12][13][14] In present study the overall success rate in Trabeculectomy with Mitomycin-C "Group A" was 67.3% while it was 83.3% with Ahmed glaucoma valve implant surgery "Group B". A study done by HaiBo T et al compared the efficacy of Ahmed glaucoma valve and Trabeculectomy with Mitomycin-C in pediatric glaucoma.…”
Section: Discussionmentioning
confidence: 57%